Wars, Guns, And Votes Democracy in Dangerous Places - Collier, Paul (Harper Collins, 2010)
Collier has made a substantial contribution to current discussions. His evidence-based approach is a worthwhile corrective to the assumptions about democracy that too often tend to dominate when Western policy makers talk about the bottom billion.â€ â€”The New York Times Book Review